Hentbol bilgi testi geliştirme, geçerlik ve güvenirliği - Bal, Merve (My University, 2023)
Bu araştırmada, spor bilimleri fakültesindeki kişilerin hentbol bilgi düzeylerini belirlemeye yönelik test geliştirilmesi amaçlanmıştır. Araştırmaya Türkiye’den beş farklı üniversitede öğrenim gören 238 kadın (Xyaş= 23,90 S= 0,83), 146 erkek (Xyaş= 24,25) olmak üzere 384 öğrenci katılmıştır. Hentbol Bilişsel Alan Testi geliştirme kapsamında 20 kazanıma ilişkin 20 konu bilgisinin ölçülmesi hedeflenmiştir. Bu yönde bir belirtke tablosu ve belirtke tablosunda yer alan kazanım ve konuları ölçmek amacıyla 75 soruluk çoktan seçmeli denemelik test hazırlanmış ve altı uzmanın görüşüne sunulmuştur. Uzman görüşlerinden sonra bazı maddelerde düzenlemeler yapılmıştır. Hazırlanan 75 soruluk denemelik test formu beden eğitimi ve spor, antrenörlük eğitimi, spor yöneticiliği ve rekreasyon derslerinde öğrencilere uygulanmıştır. Elde edilen verilere dayalı olarak madde analizleri yapılmıştır. Testin güvenirliği Kuder- Richard 20 formülü ile hesaplanmıştır. Analizler sonucunda belirtke tablosunda yer alan her bir kazanımı yoklayan en yüksek madde ayırt edicilik gücüne (> 0,20) ve orta güçlüğe (0,40-0,80) sahip 30 madde nihai test için belirlenmiştir. Hentbol bilgi düzeyini ölçmek için oluşturulan 30 maddelik bilgi testinin aritmetik ortalaması 22,61, ortalama güçlüğü 0,75 ve testin standart sapması 4,74 olarak hesaplanmıştır. Bilgi testi için hesaplanan KR-20 güvenirlik katsayısı ise 0,79 olarak bulunmuştur. Sonuç olarak, geliştirilen bilgi testinin spor bilimleri fakültesindeki öğrencilerinin hentbol bilgi düzeyini belirlemede geçerli ve güvenilir olduğu bulunmuştur.

In this study, it was aimed to develop a test to determine the handball knowledge level of the people in the faculty of sports sciences. A total of 384 students, 238 female (Mage= 23.90) and 146 male (Mage= 24.25), studying at five different universities from Turkey, participated in the study. Within the scope of Handball Cognitive Field Test development, it was aimed to measure 20 subject knowledge related to 20 acquisitions. In this direction, a specification table and a 75-question multiple-choice essay test were prepared in order to measure the achievements and topics in the specification table and presented to the opinion of six experts. After expert opinions, some articles were adjusted. The prepared 75-question test form was applied to the students in physical education and sports, coaching education, sports management and recreation classes. Item analyzes were made based on the data obtained. The reliability of the test was calculated with the Kuder-Richard 20 formula. As a result of the analyzes, 30 items with the highest item discrimination power (> 0.20) and medium difficulty (0.40-0.80) were determined for the final test, which examined each outcome in the specification table. The arithmetic mean of the 30-item knowledge test, which was created to measure the handball knowledge level, was calculated as 22.61, the mean difficulty was 0.75, and the standard deviation of the test was 4.74. The KR-20 reliability coefficient calculated for the knowledge test was found to be 0.79. As a result, it was found that the developed knowledge test was valid and reliable in determining the handball knowledge level of the students in the faculty of sports sciences.
Handball knowledge test development, validity and reliability
Keywords: Bilgi testi; Bilişsel alan; Cognitive field; Geçerlilik; Güvenirlik; Handball; Hentbol; Knowledge test; Öğrenim ve öğretim; Reliability; Study and training; Validity